The Global Biogeochemical Cycle of Arsenic. Issue 11 (23rd November 2022) - Schlesinger, William H.; Klein, Emily M.; Vengosh, Avner
Abstract: Direct exploitation and use of arsenic resources has diminished in recent years, but inadvertent mobilizations of As from mineral extractions (metal ores, coal, and phosphate rock) are now as much as ten‐fold greater (1, 500–5, 600 × 10 9 g/yr) than the As released by the natural rate of rock weathering at the Earth's surface (60–544 × 10 9 g/yr). Although some As from mining activities enters global cycling through leaching and spills, the amount of dissolved As in rivers (23 × 10 9 g/yr) is similar to the theoretical mobilization of As from chemical weathering. Anthropogenic emissions to the atmosphere (17–38 × 10 9 g As/yr) are double the natural background sources (10–25 × 10 9 g As/yr), largely as a result of the smelting of Cu and other non‐ferrous ores. This results in increased atmospheric deposition near regions with high mining and industrial activities, with potential consequences to human health, natural ecosystems and agriculture. Using median values for As, the ratio of anthropogenic to natural emissions to the atmosphere (1.57) suggests a human impact on the global As cycle that rivals those for V, Hg and Pb. Plain Language Summary: This paper compares the human mobilization of arsenic at the Earth's surface to the underlying natural flux of arsenic from rock weathering, volcanoes and other processes. Humans have roughly doubled the emission of As to the atmosphere and substantially increased the As moving in freshwaters to the sea. Key Points: The human flux of As to the atmosphere has doubled that from natural sources The human mobilization of As from mining of ferrous and non‐ferrous metals is the largest flux in the global As cycle Much of the human mobilization of As to freshwater is likely adsorbed and carried in the particulate load to the sea